Stereotactic radiation therapy for post-transplant systemic recurrence of hepatocellular carcinoma: safety, efficacy and a nomogram predicting overall survival - Chen, Jingru; Niu, Gengmin; Guo, Xin; Tao, Yuxuan; Liu, Xiaobin; Xie, Yan; Zhang, Li; Jiang, Wentao; Wang, Peiguo; Wang, Zhongqiu; Yuan, Zhiyong; Wang, Qingxin (Frontiers in Oncology, 2026)
BackgroundStereotactic Radiation Therapy (SRT) has proven effective for various stages of Hepatocellular Carcinoma (HCC), however, its role in managing intra- or extrahepatic recurrence after liver transplantation remains underexplored.ObjectivesThis study evaluates the safety and efficacy of SRT delivered using the CyberKnife® system for recurrent HCC after liver transplantation and introduces a novel nomogram for predicting survival to guide individualized management.MethodsIn a single-center retrospective study conducted between 2007 and 2020, 79 patients with recurrent HCC after transplantation presenting 133 intra- or extrahepatic lesions were treated with SRT. Treatment response, survival outcomes, and local control rates were evaluated. Multivariate analysis identified significant prognostic factors, which were incorporated into a predictive nomogram for survival.ResultsWith a median follow-up of 11.4 months, median overall survival (OS) was 15.1 months, and the local control rate was 90.5%. The OS rates at 6 months, 1 year, and 2 years were 78.9%, 57.1%, and 38.9%, respectively. Key factors associated with improved survival included fewer than three lesions, AFP <500 ng/ml, KPS ≥70, and total gross tumor volume (GTV) <40 mL. The nomogram demonstrated good predictive accuracy with a validated C-index of 0.760. Treatment was well tolerated, with no severe treatment-related toxicities observed.ConclusionSRT provides effective local control for both intra- and extrahepatic recurrences of HCC after liver transplantation. The proposed nomogram offers a valuable tool for personalized surveillance and treatment planning.